2013
DOI: 10.1177/1069072713493981
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Effects of Physical Disability Severity and Age of Disability Onset on RIASEC Self-Efficacies

Abstract: In this study, the authors focused on the context of physical disabilities (i.e., one’s age when a disability manifests and the severity with which it impacts major life activities) to better understand how disabilities influence vocational self-efficacies. Consistent with Social Cognitive Career Theory, age of onset moderated the relationship between disability severity and self-efficacies in the Realistic, Artistic, Social, and Conventional vocational domains. Specifically, disability severity had a strong, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 51 publications
1
16
0
2
Order By: Relevance
“…From the sustainable career perspective, both individual and contextual elements should be considered in career development. In terms of the contextual effect, our results found no significant linkage between family socioeconomic status and CDSE, supporting the findings of Gonzalez, Stein, and Hua [50], as well as Tenenbaum, Byrne, and Dahling's [51] studies, but being inconsistent with Hsieh and Huang's [20] findings. However, family income has been found to be positively related to CDSE, coinciding with the social cognitive career theory hypotheses that contextual factors can interact with subjective variables to affect career development [34].…”
Section: Theoretical Implicationssupporting
confidence: 75%
See 1 more Smart Citation
“…From the sustainable career perspective, both individual and contextual elements should be considered in career development. In terms of the contextual effect, our results found no significant linkage between family socioeconomic status and CDSE, supporting the findings of Gonzalez, Stein, and Hua [50], as well as Tenenbaum, Byrne, and Dahling's [51] studies, but being inconsistent with Hsieh and Huang's [20] findings. However, family income has been found to be positively related to CDSE, coinciding with the social cognitive career theory hypotheses that contextual factors can interact with subjective variables to affect career development [34].…”
Section: Theoretical Implicationssupporting
confidence: 75%
“…Metheny and McWhirter [46] reported that family socioeconomic status was positively associated with CDSE. However, Gonzalez, Stein, and Hua [50], as well as Tenenbaum, Byrne, and Dahling [51], indicated that there was no significant linkage between family socioeconomic status and self-efficacy. Scholars argue that a possible reason of the inconsistent results might be the measure used for family socioeconomic status [20].…”
Section: The Moderation Role Of Family Socioeconomic Statusmentioning
confidence: 96%
“…A study by Tenenbaum, Byrne, and Dahling (2014) recruited a sample of 153 individuals with physical disabilities in the United States by paying each participant $0.80. A study by Tenenbaum, Byrne, and Dahling (2014) recruited a sample of 153 individuals with physical disabilities in the United States by paying each participant $0.80.…”
Section: Past Research That Has Utilized Mturk To Sample From Hard-tomentioning
confidence: 99%
“…Although very few studies have used MTurk to sample from hard-to-reach populations, the studies that have been conducted suggest that this is a viable method of accessing these individuals. A study by Tenenbaum, Byrne, and Dahling (2014) recruited a sample of 153 individuals with physical disabilities in the United States by paying each participant $0.80. The authors recorded the type of disability, the age of onset, and the severity of disability of participants and then examined the independent and interactive effects of these factors on the RIASEC self-efficacy inventory (Lenox & Subich, 1994).…”
Section: Past Research That Has Utilized Mturk To Sample From Hard-tomentioning
confidence: 99%
“…Combinations of the six personality types are used to explore opportunities in which a person-environment fit presumes a higher likelihood of success or satisfaction than with non-person-environment-fit preferences (Szymanski & Van Collins, 2003). This approach to occupational interest has found application in vocational rehabilitation in acquired injury and disability (e.g., traumatic spinal cord injury — Krause, Saunders, Staten, & Rohe, 2011; mid-life disability — Tenenbaum, Byrne, & Dahling, 2014).…”
Section: Holland's Theory Of Vocational Typesmentioning
confidence: 99%